A compreensão do humor e da ironia focalizando o gênero multimodal tirinha - Frota, Leandra Cristina Cavalcante (2023)
The present work has the general objective of expanding reading comprehension skills from the use of multimodal texts, such as the comic strip, proposing activities for the development of reading skills from the use of strips of Turma do Armandinho with 9th grade students, in order to improve the SPAECE results, which are at a critical level, and consequently the performance of learners in mother tongue studies. The pedagogical device used is the didactic itinerary, which seeks to expand students' language activities, allowing the realization of pedagogical projects and the use of different genres in the process, according to Dolz et al (2020). The main focus of the study is the recognition of the effects of humor and irony, descriptor (D22) located in the topic of relations between expressive resources and effects of meaning of the SPAECE´s Reference Matrix. Our research is based on the theoretical assumptions of Sociodiscursive Interactionism, in which Broncarkt (1999) and the ISD bring language teaching into a social context in which interaction occurs. The theoretical contribution will make use of authors such as Leurquin (2001), Solé (1998), Kleiman (2001) and Braggio (1992) for deepening in the conceptions and reading strategies, Possenti (2010) regarding the understanding of humor; as well as in Kress and Van Leeuwen's (2006) social semiotics and Grammar of Visual design, since it is not enough to identify the image, but to read and interpret it to understand the discursive implications. The work has a propositional character, since at the end of the studies and appropriation of theories through documentary and bibliographical research, a didactic notebook was developed in order to collaborate for the improvement of the results indicated in the external evaluations and consequently in the development of the learners.